Factors determining peat thickness in secondary forest of Kuan Kreng peat forest, Southern Thailand - Meunpong, Ponthep; Wachrinrat, Chongrak; Wanthongchai, Kobsak (Agriculture and Natural Resources, 2020)
In Thailand, increased demand has forced the conversion of peat forest to agricultural area. As a result, drainage canals have been dug in peat forests without any control on their effect on the level of groundwater, increasing the risk of forest fire. Peat volume estimation as a fuel source for forest fires is required for specific prevention programs, such as fuel management. Inventories of peat depths and environmental factors such as forest stand biomass were made in the Kuan Kreng peat forest, Southern Thailand to evaluate the peat depth using estimated parameters instead of direct measurement. The results were tested against a dataset of 171 plots on a 1 km sampling grid. The average peat depth was 0.78 m with the deepest location estimated at 3.10 m. Peat depth could be modelled using vegetation data, combined with both litter mass (tonnes per hectare) and height of vegetation ground cover (meters). The regression model developed to predict peat depth was: Peat depth (m) = 0.436 + 0.19 (litter mass) + 0.236 (ground cover depth). In general, the predicted peat depth was over-estimated and at times, predictions were outside the observed data range. This was attributed to additional effects from both internal and external parameters on peat formation that had not been included in the model. In addition, it is important to maintain a certain height of water table to prevent fire and encourage natural revegetation.